2018
DOI: 10.1155/2018/7845681
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Attenuates Cardiomyopathy in Streptozotocin‐Treated Diabetic Rats

Abstract: Diabetic cardiomyopathy is a diabetic complication due to oxidative stress injuries. This study examined the protecting influence of thymoquinone (TQ) on diabetes-caused cardiac complications. The intracellular means by which TQ works against diabetes-caused cardiac myopathy in rats is not completely understood. In this study, Wistar male rats (n = 60) were assigned into four groups: control, diabetic (diabetes induced by IP infusion of streptozotocin, 65 mg/kg), diabetic + TQ (diabetic rats given TQ (50 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 47 publications
3
36
1
Order By: Relevance
“…Furthermore, reduction in hypertriglyceridemia applying fibrates therapy can abate UAER rise in T2DM patients [37]. Expectingly, HSYA can significantly lower the level of blood lipid profile in T2DM rats in our study, which has a similar result with the previous study [38]. Taken together, HSYA could ameliorate hyperlipemia and suppresses the inflammatory response by reducing the accumulation of inflammatory product.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, reduction in hypertriglyceridemia applying fibrates therapy can abate UAER rise in T2DM patients [37]. Expectingly, HSYA can significantly lower the level of blood lipid profile in T2DM rats in our study, which has a similar result with the previous study [38]. Taken together, HSYA could ameliorate hyperlipemia and suppresses the inflammatory response by reducing the accumulation of inflammatory product.…”
Section: Discussionsupporting
confidence: 87%
“…Feeding with HFD could induce hyperlipemia and insulin resistance, 20,21 HSYA-treatment not only decreased FBG but had the anti-hyperlipidemic effect which would improve insulin resistance indirectly. Although HDL-C had the antioxidant and anti-inflammatory effects 22 and some studies 23,24 showed that the HDL-C level in T2DM rats would be higher than that of the normal rats, our founding suggested that there was no statistical difference between them as the previous study. 25 In this study, the T2DM rats indicated a decrease in acinar staining intensity that reflecting the defects in digestive function of the pancreas.…”
Section: Discussioncontrasting
confidence: 46%
“…In addition, TQ alleviates diabetes-associated oxidative stress in cardiac tissues [8]. Additionally, several studies have shown that the protective effect of TQ against cardiac damage such as in case of ischemic damage [9] and acute abdominal aortic ischemia-reperfusion injury [10]is mediated via the pyroptosis pathway [11].…”
Section: Several Researchers Have Investigated Various Drugs For Treamentioning
confidence: 99%